Implementation of chemical injection with WJSTP in the Gullfaks field attributed to reservoir permeability - Metsebo, Jules; Tsapla Fotsa, Rolande; Tsamo, Nestor; Djembo, Jean Aimé; Komofor Ngopuh, Finalise; Chéagé Chamgoué, André (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
The Gullfaks field is a complex field and it’s divided into several formations, which have reservoirs in several stratigraphic layers and fragments of numerous faults. With current technological advancement techniques used in the Gullfaks field, the WJSTP is one of the solution-testing platforms that focuses on treating produced water for re-injection back into the reservoir to increase oil production. The implementation of chemical injection with WJSTP in the Gullfaks field, attributed to reservoir permeability to increase oil production, is the aim of this paper. To attest to the set aimed, a three-dimensional static model of the reservoir is constructed using data provided by NGB Geosciences Consulting LTD. With credit to the Petrel software simulation tool, an in-place volume estimate of 2,748,727,672.95 Bbls of oil and 970,264,150,943.39 SCF of gas was reviewed. Subsequently, a dynamic model is constructed on the foundation of the static model and the specified water injection parameters, and simulated with the use of the Eclipse software. The reduction in permeability of the reservoir's high-permeability zones through chemical injection of WJSTP resulted in 70% oil recovery, representing a 44.99% increase, and 74% gas recovery, representing a 37.9% increase. The sensitivity analysis conducted on oil price, oil production, and investment demonstrates that the viability of the project is highly contingent on the oil price. The findings of this study indicate that chemical injection of WJSTP represents a technically feasible and economically profitable method of enhancing oil production in the Gullfaks field.